Gaya Bahasa Tauriyah Dalam al-Qur'an - Yuangga Kurnia Yahya (Institut Agama Islam Negeri Curup, 2018)
This paper aimed to research about Badi’ style in al-Qur’an’s passages. This research used one aspects of Balaghah, tauriyah, and spoke about al-Qur’an’s passages which contains tauriyah style dan the secret behind its using. The objects of this research come from al-Qur’an’s passages using style of language/balaghah analysis, especially Ilmu Badi’ which concentrated to beauty of meaning (muhassinaat ma’nawiyyah) and importance of understanding tauriyah for another studies focused their object based on al-Qur’an, directly or not. This paper find that there are at least 10 passages which contains tauriyah in al-Qur’an, they are al-Baqarah: 143, al-An’am: 60, at-Taubah: 21, Yunus: 92, Yusuf: 42, Yusuf: 96, Thaha: 5, adz-Dzariyat: 47, ar-Rahman: 6 and al-Ghasiyah: 8. This number of passages erase the old paradigm that recognite only 3 passages in al-An’am: 60, Thaha: 5 and adz-Dzariyat: 47. Understanding tauriyah became important in Tafsir studiy and isthinbatu’l ahkaam in Ushu’l Fiqh field, even became one of obligatory requirements for mujtahid.